The theme of Survival In Phyllis Gotlieb’s Birthstones (2007): An Eco-Feminist Analysis (Journal of Imam Al-Kadhim College, 2023)
The study investigates the theme of survival in Phyllis Gotlieb’s Birthstones (2007), a science fiction addressing issues such as environment, community, and ecological catastrophes. It argues that survival is imagined in the face of environmental apocalypse by the Canadian woman science fiction Phyllis Gotlieb.  Survival is examined from the perspective of women and non-human nature, who have traditionally been the object of scientific experimentations. Birthstones deals with survival of the planet Shar and its community in which both women and the environment are oppressed and degraded. Survival of the planet is threatened by the breakdown of the environment and the family. The novel presents the disintegration of society in general and the family in particular when moms are absent. Due to environmental catastrophes, the women of the Shar planet are deformed, and consequently they are treated as non- human creatures and considered by the government only as womb capsules. They are taken away from their families for scientific experimentations as soon as they deliver their babies. Similarly, the Shar planet is polluted and the land is used for mining only and is exploited by other aliens. The government exploit both women and the land. Instead of protecting the environment from pollution, the leaders wear the masks to protect themselves only, leaving the planet suffer from infertility and birth abnormalities. The study is a call for keeping the environment healthy by stopping polluting it and by taking care of the mothers by keeping them in their houses to raise their children and take care of their families. Only in this way survival of the society and the planet is achieved.
Keywords: Keywords: science fiction, eco-feminism, motherhood, survival, environmentalism